INFLUENCE OF MARKETING RELATIONSHIPS, CUSTOMER VALUE, AND TRUST ON CUSTOMER LOYALTY (CASE STUDY ON USERS OF BPJS HEALTH BATU ROTOK VILLAGE) - Abdul Salam; Adi Susanto (Universitas Islam Lamongan, 2022)
This study aims to test the effect of relationship marketing, customer value, and trust on customer loyalty at BPJS Kesehatan customers in Baturotok village, Sumbawa Region. Samples in the study earned with nonprobability sampling were announced to 100 respondents. The research uses the quantitative method. The data obtained were analyzed techniques through software SPSS 16. The results of the analysis in this study indicated that (1) the relationship marketing variable of use has significant customer loyalty. (2) variable customer value has no effect and is not significant has customer loyalty. (3) variable trust no effect and not significant have customer loyalty.